Variable structure control for a continuous bioreactor - Tham, H.J.; Hussain, Mohd Azlan; Ramachandran, K.B. (2000)
Fermentation is known to be a highly nonlinear process and it requires a nonlinear controller for effective control. This paper studies the application of variable structure control or sliding mode control with direct use of nonlinear model to a continuous baker's yeast production. Lyapunov's theorem is used to ensure asymptotic stability of the system, and also to determine the switching coefficients of the controller. The switching coefficients are calculated and determined during the process. To overcome chattering, the control input derivative is used as an auxiliary variable. The simulation results show smooth response for set point change. For external disturbance rejection, it was found that the controller is able to bring the state back to the sliding surface, and the state is maintained there for the subsequent time.